Peer Correction On Writing Quality Of College Students Having Different Cognitive Styles - Sri Wahyuni (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2018)
Correction in writing process is beneficial to improve students’ writing quality. However, different kinds of correction may affect students’ writing quality differently. Furthermore, depending on their cognitive style, students may receive correction differently. This research aims at investigating the effect of peer correction on writing quality of college students’ having different cognitive styles. Two groups of students participated in this study. In the treatment, one group conducted peer correction, and the other group conducted self correction on their writings. To collect the data on students’ cognitive styles, Group Embedded Figure Test (GEFT) was used. To collect the data on students’ writing quality before and after the treatment, writing tests were used. To test the hypotheses, an analysis of covariate (ANCOVA) was used. The results shows that both types of corrections, peer and self corrections, and students’ cognitive styles, field dependent and field independent, significantly affects the students’ writing quality. However, it seems to be no significant interaction between types of corrections and students’ cognitive styles. The types of correction and cognitive styles do not affect students’ writing quality at the same time.